Community structure and environmental determinants of the bacterial and fungal gut microflora in Hainan gibbons (Nomascus hainanus) - Liangliang Yang; Wenxia Wang; Torsten Wronski; Ping Sun; Kun Jin; Weilu Tang (Global Ecology and Conservation, 2022)
High-throughput sequencing technology was used to establish the OTU (Operational Taxonomic Units) composition and diversity of bacteria and fungi in the gut of three family groups of Hainan gibbons (Nomascus hainanus) in the Bawangling National Nature Reserve on Hainan Island, southern China. Firmicutes (47.23%) and Bacteroidetes (36.54%) predominated at the phylum level, while the predominant genera were Prevotella-7 (15.30%), Lachnospiraceae_NK3A20_group (12.49%), and uncultured_bacterium_f_Erysipelotrichaceae (11.79%). At the phylum level, the dominant fungi were Ascomycota (66.41%), as well as Hanseniaspora (23.33%), Schwanniomyces (13.44%), and Pichia (5.43%) at the genus level. We found significant differences in the bacterial OTU diversity (Shannon index) between family groups living in Tropical Lowland or Tropical Montane Rain Forest, compared to those inhabiting Tropical Montane Evergreen Forest at higher altitudes. Bacterial OTU community composition also differed between family groups, unraveling significant differences among the 30 most dominant bacterial core taxa. Furthermore, we unraveled a significant difference of OTU richness in the fungal microbiome (Chao 1) between family groups living at lower altitudes, i.e., Tropical Lowland or Tropical Montane Rain Forest and those inhabiting the Tropical Montane Evergreen Forest. Our analysis further indicated significant differences in the fungal OTU community composition between the three family groups, especially regarding the three most dominant fungal core taxa. Subsequently, two habitat factors, and nine environmental and anthropogenic variables were used to explore possible causes of disparity in the microbial flora of gibbon groups. A factor reduction procedure resulted into three principal components which were correlated to bacterial and fungal OTU richness and diversity using Spearman's rank-order correlations. Bacterial and fungal OTU diversity was high in areas of high altitude, steep slopes, high tree density, but low tree height, while high fungal OTU richness corresponded to high altitude habitats, i.e., in the Tropical Montane Evergreen Forest. Distance to human settlements and to the next water body showed no significant relation with bacterial and fungal richness and diversity.